Becoming artist-teacher: the educational turn of art (Revista Apotheke, 2024)
This article is an excerpt from doctoral research that analyzes the impact of the imbrication between art and teaching on the constitution of the teacher-artist hybrid. The central aim of this investigation is to trace the panorama that made the educational turn in art possible. This research is justified by the valorisation of art as knowledge, as well as reflecting on the influences of contemporary art on teaching and the creation of alternative modes of learning in recent decades. With this in mind, it begins with an analysis of how and when education began to move artistic practice, based on an analysis of the actions of Joseph Beuys and Lygia Clark, and then looks at how this concept was established and operates today. For this purpose, a methodological approach of bibliographical, documentary and exploratory research is used. The theoretical basis used is Luis Camnitzer (2009), Tatiana Fernández (2016), Nina Simon (2010), as well as Paul O’Neill and Mick Wilson (2010).
Keywords: art; educational turn; artist-teacher; education